Perlunya Perubahan Pendekatan Dalam Implementasi UU No. 33 Tahun 2014 Tentang Jaminan Produk Halal: Produk Kebijakan Publik Yang Perlu Ditinjau? Penelitian - Bambang Sumaryanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The implementation of Law No. 33 of 2014 concerning Halal Product Guarantee (JPH Law) faces various challenges, especially in the micro and small industry (IMK) sector for food and beverages. This study uses a descriptive method with literature study and secondary data from previous studies, analyzed qualitatively. Although the government has launched programs such as Free Halal Certification (SEHATI) and a self-declare scheme, the participation of MSME business actors remains low. Low awareness and involvement of business actors are the main obstacles. Policy evaluation using Weiss's Benefit Theory approach shows the importance of actively involving business actors from the planning to evaluation stages, with a focus on direct benefits for them. On the other hand, the March & Olsen approach emphasizes the importance of the role of institutions and structured decision-making processes. This study concludes that a change in approach to policy implementation, through synergy between individuals, institutions, and stakeholders, is key to the successful implementation of the JPH Law as a whole. Without such changes, there are concerns that the target of full implementation by October 17, 2026, will not be achieved.